The Effect of Green Marketing on Repurchase Intention of Le Minerale Products in Palu City Through Brand Image as an Intervening Variable - Wahyunga, Wahyunga; Parani, Syamsul Bachri Dg; Santi, Ira Nuriya; Asriadi, Asriadi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This study aims to analyze the extent to which green marketing implemented by Le Minerale can influence consumer repurchase intention in Palu, and how brand image can strengthen or mediate the relationship. The method used in this study is quantitative with a descriptive causality research type and SEM-PLS version 4.0 analysis technique. The sampling technique used is a non-probability sampling technique through purposive sampling, with a sample size of 120 consumers who purchased Le Minerale water products in Palu and were willing to be respondents to fill out the questionnaire that had been submitted, by determining certain characteristics that were in accordance with the objectives of the study. The results showed that green marketing had a positive and significant effect on repurchase intention of Le Minerale products in Palu, green marketing had a positive and significant effect on brand image of Le Minerale products in Palu, and brand image had a positive and significant effect on repurchase intention of Le Minerale products in Palu. Green marketing had a positive and significant effect on repurchase intention through the brand image of Le Minerale products in Palu.